2009
DOI: 10.1681/asn.2008070806
|View full text |Cite
|
Sign up to set email alerts
|

TβRI Independently Activates Smad- and CD2AP-Dependent Pathways in Podocytes

Abstract: TGF-␤ regulates differentiation, growth, and apoptosis of podocytes and mediates podocyte depletion in glomerulosclerosis. TGF-␤ promotes proapoptotic signaling mediated by Smad3 but also activates prosurvival pathways such as phosphoinositide-3 kinase (PI3K)/AKT; the latter requires the CD2-associated adaptor protein (CD2AP) in podocytes. Whether the opposing activities mediated by Smad proteins and CD2AP involve molecular cross-talk is unknown. Here, we report that CD2AP-dependent early activation of the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Lamouille et al (41) observed that translational regulation of epithelial-mesenchymal transition genes is mediated by TGF-␤-induced mTOR activation through PI3K and Akt. Akt is considered a prosurvival pathway, and TGF-␤1 is known to activate Akt through CD2AP in podocytes (52). Similar to the observation by Abe et al (53), we detected TSC2 phosphorylation at Thr 1462 .…”
Section: Volume 290 • Number 52 • December 25 2015supporting
confidence: 91%
“…Lamouille et al (41) observed that translational regulation of epithelial-mesenchymal transition genes is mediated by TGF-␤-induced mTOR activation through PI3K and Akt. Akt is considered a prosurvival pathway, and TGF-␤1 is known to activate Akt through CD2AP in podocytes (52). Similar to the observation by Abe et al (53), we detected TSC2 phosphorylation at Thr 1462 .…”
Section: Volume 290 • Number 52 • December 25 2015supporting
confidence: 91%
“…8B) (56,57,60,61). We also found that TGF-␤1 increased expression of ErbB4 and increased ErbB4 phosphorylation (Tyr-984), suggesting that it elicits intracellular signaling.…”
Section: Mir-146 In Podocytes and Diabetic Injurymentioning
confidence: 52%
“…It can induce foot process effacement of podocytes and lead to cytoskeletal damage and abnormal molecular expression and distribution of podocytes. [6][7][8][9][10][11][12] In this study, we established podocyte injury models using Ang II in this part of the study by referring to the previous work of our group. 13,14 The experimental results demonstrated that the Ang II stimulation group showed foot process retraction at eight hours, and the cell area is reduced to 38.9% of the control group; the foot process significantly was reduced at 24 hours' stimulation, and the cell area declined to 5% of the control group; after stimulation for 48 hours, the cell area declined to 4.5% of the control group, and part of the podocytes showed foot process effacement and loss of intercellular junctions.…”
Section: Discussionmentioning
confidence: 99%